Collaborative Mentoring to Strengthen Pedagogical Competence at SMP Negeri 11 Ambon - Paul Arjanto; Rudolf Kempa; Patrisius Rahabav; Lambertus Johanes Lokollo; Beatrix Tomasila; Vando Kristi Makaruku; Estin Indria Maahury; Nandalita Nunuela; Adha Marche Lino Untajana (DEVOTIONIS, 2026)
Teachers' pedagogical competence was a strategic determinant of instructional quality, especially in schools adapting to flexible, student-centered curriculum reform. This community service article reported the initial implementation of a collaborative mentoring program for teachers at SMP Negeri 11 Ambon, Amahusu, Ambon City. The activity aimed to strengthen teachers' understanding of pedagogical competence, active learning, participatory classroom management, and the use of simple and digital learning media. A community-based service design was applied through preparation, implementation, and evaluation stages. Data were collected through coordination notes, participatory observation, teaching document review, reflective discussion, and a simple participant response questionnaire. The implementation consisted of a mini-seminar, interactive group discussion, case analysis of teaching documents, and collective reflection. The results showed that the mentoring process helped teachers identify the gap between administrative lesson planning and meaningful instructional design. Teachers became more aware of the need to align learning objectives, student characteristics, learning activities, learning media, and formative assessment. The collaborative forum also encouraged peer exchange and produced an initial classroom follow-up plan. The main outputs included a pedagogical competence strengthening module, an implementation flow model, and a descriptive monitoring framework for school-based reflection. The program concluded that collaborative mentoring was feasible as an entry strategy for teacher professional development in an island-based school context. Future activities should include longer workshops, classroom coaching, microteaching, and measurable evaluation of competence improvement.